Impact of Laser Capsulotomy in the Quality of Life of the Elderly with Posterior Capsule Opacity after Cataract Surgery - Armando Rafael Milanés Armengol; Kattia Molina Castellanos; Inés Zamora Galindo; Alina González Díaz; Maikelyn Rodríguez Hernández (Medisur)
Background: the opacity of the posterior lens capsule after cataract surgery has decreased in recent years but its incidence remains high. Objective: To assess the impact of the opacification of the posterior lens capsule and its treatment with laser capsulotomy on visual function and life quality of patients after cataract surgery. Methods: A case series study of elderly patients with diagnose of opacity in the posterior lens capsule after cataract surgery who were treated with laser capsulotomy from January 2010 to January 2011 in the General University Hospital of Cienfuegos was conducted. A survey and a battery of assessment tools to measure functional status were applied as well as the VF-14 test for the assessment of life quality. Results: We observed an improvement in the average value of the visual acuity (0, 326 by 0, 726 practiced capsulotomy to later), with an average range of efficiency improvement of a binocular visual 6.96%, likewise improved functional visual capacity from 57, 728 to 96, 223; exploration by VF-14 showed a higher life quality. The degree of overall validism was recovered in 86, 56 % of patients and only one patient was totally dependent for the realization of daily life activities. Conclusions: Patients who underwent laser capsulotomy showed evidence of improvement in visual acuity, functionality and life quality.